First fossil record of Atherinella sp. (Pisces, Teleostei, Atherinopsidae) from the Lower Pliocene of Costa Rica, Central America - Flores, Hector (2018)
A fossil specimen of Atherinella collected from Lower Pliocene tuffites deposits of the Bagaces Formation outcropping near of Las Juntas city, in Guanacaste province, is described. This found suggests a brackish estuarine environment which is in concordance with the previous observations based on the fossil record of marine invertebrates from other locations of this formation. This new record fossil is important to understand the recent biogeographic distribution of genus, which it probably was due to tectonic events.